Time Spent on Private Tutoring and Sleep Patterns of Chinese Adolescents: Evidence from a National Panel Survey - Yueyun Zhang (MDPI AG, 2023)
Objective: In recent decades, there has been a marked increase in private tutoring and a decline in sleep health among adolescents. This study aimed to outline the association between time spent on private tutoring and sleep patterns of Chinese adolescents. Methods: Participants were from a nationwide two-wave panel survey. We performed OLS regressions of sleep duration at wave 2 and Poisson regressions of sleep problems at wave 2 on tutoring time at wave 2, adjusting for baseline sleep duration and other covariates. Tutoring time was assessed by three items: daily hours of tutoring, daily hours of tutoring on weekdays, and daily hours of tutoring on weekends. Results: Overall, more time spent on private tutoring was associated with shorter sleep duration and more sleep problems. Furthermore, both weekday and weekend tutoring can have a positive effect on the number of sleep problems. With regard to sleep duration, weekend tutoring time played a negative role, while the effect of weekday tutoring time was negligible. Conclusion: In the Chinese context, which is characterized by intense academic competition, participation in private tutoring plays a significant role in shaping students' sleep duration and sleep problems. To improve the sleep health of adolescents, the time spent on private tutoring should be carefully monitored and regulated.